Personal emergency alarms: do health outcomes differ for purchasers and nonpurchasers?. Issue 3 (2nd October 2017) - De San Miguel, Kristen; Lewin, Gill; Burton, E lissa; Howat, Peter; Boldy, Duncan; Toye, Christine
ABSTRACT: The objective of this study was to assess whether purchasing a personal alarm service makes a difference in a range of health outcomes for community dwelling older adults. The prospective cohort study involved 295 individuals for whom data on emergencies experienced at home were collected over a period of 12 months. Purchasers of alarms, compared to nonpurchasers, benefitted in terms of feeling more safe and secure and being more active around their home. Outcomes experienced after an emergency were similar for both groups with no differences found in terms of time spent on floor, or hospitalizations.